2007
DOI: 10.1074/jbc.m705608200
|View full text |Cite
|
Sign up to set email alerts
|

A Peptide Derived from Tenascin-C Induces β1 Integrin Activation through Syndecan-4

Abstract: Tenascin-C (TN-C) is unique for its cell adhesion modulatory function. We have shown that TNIIIA2, a synthetic 22-mer peptide derived from TN-C, stimulated ␤1 integrinmediated cell adhesion of nonadherent and adherent cell types, by inducing activation of ␤1 integrin. The active site of TNIIIA2 appeared cryptic in the TN-C molecule but was exposed by MMP-2 processing of TN-C. The following results suggest that cell surface heparan sulfate (HS) proteoglycan (HSPG), including syndecan-4, participated in TNIIIA2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
116
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(120 citation statements)
references
References 42 publications
3
116
1
Order By: Relevance
“…Anoikis-NIH3T3 cells adhere to the fibronectin substratum mainly via integrin ␣5␤1 (28). When NIH3T3 cells adhering to the fibronectin were cultured under serum-starved conditions, the number of viable cells decreased in a time-dependent manner, which was in parallel with an increase in the detached cell number (Fig.…”
Section: Proteolytic Exposure Of the Cryptic Antiadhesive Site Withinmentioning
confidence: 53%
See 2 more Smart Citations
“…Anoikis-NIH3T3 cells adhere to the fibronectin substratum mainly via integrin ␣5␤1 (28). When NIH3T3 cells adhering to the fibronectin were cultured under serum-starved conditions, the number of viable cells decreased in a time-dependent manner, which was in parallel with an increase in the detached cell number (Fig.…”
Section: Proteolytic Exposure Of the Cryptic Antiadhesive Site Withinmentioning
confidence: 53%
“…For cell adhesion, cells suspended with the serum-free medium with or without the sample to be tested were seeded onto a 96-well plate coated with fibronectin, incubated for 30 -60 min, and then fixed with formalin. After washing off unadhered cells, cells adhered to the fibronectin substratum were counted as described previously (28). For ␤1-integrin activation, activation of ␤1 integrins on the cells was evaluated by flow cytometric analysis (FACS Aria, BD Biosciences) using 9EG7, a monoclonal antibody recognizing the active ␤1-integrin conformation-specific epitope (29), as described previously (18).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, a 22mer fusion peptide containing an adhesive YTITIRG sequence bound to the heparin sulfated side chains of the b1 integrin co-receptor synecan-4, hence inducing cell adhesion and spreading on FN. 132 This study found that mutation of the cytosolic region of syndecan-4 had no effect on promoting the inhibition of b1 integrin action, suggesting the extracellular portion of syndecan-4 binds FNIII-A2 and hence promotes b1 integrin clustering and activation, rather than mediating this effect via downstream targets of syndecan-4. Elevated levels of both activated MMP-2 and degraded tenascin-C were identified in NSCLC, with proteolytically degraded tenascin-C serving as a good indicator of stage-1 NSCLC recurrence.…”
mentioning
confidence: 88%
“…[8][9][10][11][12][13] However, the complete molecule is considered anti-adhesive. This function has been mapped primarily to the EGFL component of TNC.…”
Section: Tnc Signaling Germane To Melanoma Invasion and Survivalmentioning
confidence: 99%